2008
DOI: 10.1073/pnas.0710262105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic royal cheats in leaf-cutting ant societies

Abstract: Social groups are vulnerable to cheating because the reproductive interests of group members are rarely identical. All cooperative systems are therefore predicted to involve a mix of cooperative and cheating genotypes, with the frequency of the latter being constrained by the suppressive abilities of the former. The most significant potential conflict in social insect colonies is over which individuals become reproductive queens rather than sterile workers. This reproductive division of labor is a defining cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
124
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 32 publications
0
124
3
1
Order By: Relevance
“…Those relevant for domain 1 are reviewed in Burt & Trivers (2006) and those relevant for domain 2 in Buss (1987) and Michod (2005). Threats of domain 3 may include workers that reproduce in the presence of the queen and socially parasitic additional queens that may ultimately give rise to inquiline species (Buschinger 1990) and selfish patrilines (Hughes & Boomsma 2008 . Schematic comparison of the evolutionary transition from unicellularity to multicellularity and the evolution of eusociality in the haplodiploid ants (the same applies to bees and wasps) and diploid termites.…”
Section: Discussionmentioning
confidence: 99%
“…Those relevant for domain 1 are reviewed in Burt & Trivers (2006) and those relevant for domain 2 in Buss (1987) and Michod (2005). Threats of domain 3 may include workers that reproduce in the presence of the queen and socially parasitic additional queens that may ultimately give rise to inquiline species (Buschinger 1990) and selfish patrilines (Hughes & Boomsma 2008 . Schematic comparison of the evolutionary transition from unicellularity to multicellularity and the evolution of eusociality in the haplodiploid ants (the same applies to bees and wasps) and diploid termites.…”
Section: Discussionmentioning
confidence: 99%
“…This z-statistic is the effect size for a particular colony and has the desirable property that the null expectation is a standard normal distribution. From earlier studies of A. echinatior (20,23), E. burchellii (22), P. badius (21,24), F. exsecta, and F. truncorum (62), we calculated the heterogeneity G-statistic and the exact probability, the effect size for each colony in the study, and the 95% confidence interval of the mean effect size (across colonies) for each species. Data for a recent similar study in P. rugosus (29) were not presented in a form that allowed calculation of appropriate statistics.…”
Section: Methodsmentioning
confidence: 99%
“…A similar phenomenon occurs in hybridizing populations of fire ant species (19). In these species, there is a clear genetic effect.A second set of studies involves species with polyandrous queens that find differences in the distribution of male genotypes between gynes and workers or between workers belonging to different castes (20)(21)(22)(23)(24). The general pattern is to find that in some, but not all, colonies the distribution of male genotypes (patrilines) differs significantly between castes, leading to a significant overall difference when results are pooled across colonies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though recent studies revealed genetic influences on caste determination in social insects (reviewed in ref. 26), female caste fate is primarily influenced by environmental factors in most species studied (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In ants, several studies suggested that maternal factors such as temperature or queen age may affect caste determination (40)(41)(42)(43)(44).…”
mentioning
confidence: 99%